2023
DOI: 10.1038/s41467-023-37926-7
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated vaccine-elicited potent antibodies can broadly neutralize SARS-CoV-2 circulating variants

Abstract: A full understanding of the inactivated COVID-19 vaccine-mediated antibody responses to SARS-CoV-2 circulating variants will inform vaccine effectiveness and vaccination development strategies. Here, we offer insights into the inactivated vaccine-induced antibody responses after prime-boost vaccination at both the polyclonal and monoclonal levels. We characterized the VDJ sequence of 118 monoclonal antibodies (mAbs) and found that 20 neutralizing mAbs showed varied potency and breadth against a range of varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 101 publications
3
32
0
Order By: Relevance
“…Our antibody array primarily consists of memory B-cell derived antibodies that are studied to be broadly neutralizing against different variants (23, 24, 30). Our results support the empirical results that our antibody array, primarily consisting of broadly neutralizing antibodies, maintains their efficacy across different variants (23, 24, 30). The presence of such broadly neutralizing antibodies also may indicate a level of prevalence of memory B-cells within vaccinated individuals that generate such antibodies (23, 30, 50, 51).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our antibody array primarily consists of memory B-cell derived antibodies that are studied to be broadly neutralizing against different variants (23, 24, 30). Our results support the empirical results that our antibody array, primarily consisting of broadly neutralizing antibodies, maintains their efficacy across different variants (23, 24, 30). The presence of such broadly neutralizing antibodies also may indicate a level of prevalence of memory B-cells within vaccinated individuals that generate such antibodies (23, 30, 50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Other available SARS-CoV-2 Spike RBD crystal structures were downloaded from the Protein Data Bank (PDB) (21). We derived the WT and BA.1 RBD structures from the Protein Data Bank as they represent empirically derived structures from an RBD-Antibody or RBD-ACE2 complex (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). B.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, the CoronaVac inactivated vaccine with alum adjuvant demonstrated highly effective neutralizing effects against SARS-CoV-2. 104…”
Section: Inactivated Vaccinesmentioning
confidence: 99%